Stabilization of pre‐optimized multicolor antibody cocktails for flow cytometry applications. Issue 6 (11th May 2016) - Chan, Ray Chun‐Fai; Kotner, Joshua S.; Chuang, Christine Ming‐Hui; Gaur, Amitabh
Abstract : Background: Flow cytometry has a multitude of applications in nearly all fields of biology. Newly described biological markers enable the creation of novel reagents which then aid in the elucidation of unique subsets of cells and their potential role in health and disease. In order to enable the simultaneous detection of an even greater number of parameters, the future progress of flow cytometry relies on advances in instrument engineering and the parallel development of new fluorophores. Methods: In order to address the issues of reagent reliability, reproducibility, and work‐flow optimization, we have used the freeze‐dry technique to stabilize pre‐mixed, pre‐optimized, multicolor 'cocktails' of antibodies within 12 × 75 mm flow cytometry tubes (Lyotube). In this study we describe several lyophilized stabilized reagent combinations that are functional for extended periods of time (18 months and beyond), and can be stored at ambient temperature, eliminating cold‐chain requirements during transportation and storage. This improves precision and reduces the redundant labor and error‐potential associated with mixing antibodies to create "home‐brew" cocktails. Results: We have stained different types of samples including normal and leukemic whole blood, bone marrow, and PBMCs, as well as cell lines, directly with BD Lyotube reagents: The data show comparable and consistent performance of multiple batches of dehydrated, stabilized mixtures of antibodies and their liquid counterparts. Conclusions: The approach we describe here, the Lyotube, facilitates the improvement and implementation of standardization measures in clinical settings and in multi‐site studies, a useful tool which can also be applied to determining the efficacy and safety of candidate therapeutics and vaccines. © 2016 International Clinical Cytometry Society